ANALISIS PENOKOHAN DALAM NOVEL SELEMBAR DAUN MOMIJI KARYA ARIZU KAZURA - Hernimawati Zebua (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2025)
This research is motivated by analytical and dramatic variations in the characters' characters. The characters in the novel Selembar Daun Momiji by Arizu Kazura, cause readers to become more curious about the continuation of the characters' characters and the characters in the novel Selembar Daun Momiji by Arizu Kazura, are difficult to interpret and this is the reason why researchers want to analyze the characters in the novel Selembar Momiji Leaves by Arizu Kazura. This research aims to describe the characterization of the characters in the novel Selembar Daun Momiji by Arizu Kazura. The approach used in this research is qualitative with a content analysis method. The data source in this research is the novel Selembar Daun Momiji by Arizu Kazura. The data collection technique for this research is documentation. The data analysis techniques in this research are data reduction, data presentation and conclusions/verification. The findings of this research show that the results of analytical analysis in the Novel Selembar Daun Momiji by Arizu Kazura have nine Yamada characters, five Ryoko characters and five Akira characters, while the results of the dramatic analysis of characterization in the Novel Selembar Daun Momiji by Arizu Kazura have five characters, namely Yamada, Ryoko, Akira, Keici and Hikari. Yamada's character is fair-skinned, handsome, responsible, doesn't force other people's will, has a good temper, is caring, likes to praise and pays attention, Ryoko has the character of being helpful, giving attention, likes to praise, has a good temper, likes to be sad, for nine years has closed herself off and lived a lie, Akira has a good-tempered character, does not force other people's wishes, likes to praise, cares and hurts for friends, Keici has a character who likes to help, is considerate and caring, Hikari has a character who is worried, affectionate and gives encouragement). The researcher's suggestion is that the findings of this research should be used as a comparison material for future researchers. and it is hoped that it can provide additional new insights in the field of Indonesian literary language, especially the form of mandate.